(untitled) (The Geographic Base, 2022)
The government of Nepal has been implementing policies to increase agriculture production by motivating farmers towards farming. This study aims to identify spatially distributed suitable areas for sustainable Arabica coffee production in the Gulmi, Palpa, Arghakhanchi, and Pyuthan districts of Lumbini Province. The multi-criteria analysis was carried out to identify the suitable area for coffee cultivation in the study area, where parameter values were assigned based on Analytical Hierarchy Process (AHP). In the AHP method, the weightage for each parameter for suitability was considered through an expert questionnaire, interview, and field observation. The modeled suitability map was verified through field inventory-based coffee farm points. The result shows different land suitability classes: highly suitable (S1), moderately suitable (S2), marginally suitable (S3), and not suitable (N) cover an area of 869.0 km2 (16.92%), 1949.0 km2 (37.95%), 280.23 km2 (5.46%), 2037.00 km2 and (39.67%), respectively. The suitable areas are equally distributed around the study area, while some agglomeration patches were observed in northern Arghakhanchi and southern Gulmi. The findings of this study can be used for coffee production and to gain related economic benefits in the study area. The condition of precipitation, soil characteristics, and topography of the study area are much favorable to Arabica coffee hence farmers need to consider growing Arabica coffee rather than Robusta-type coffee.